"As Raw As It Can Be, Like Vulnerable and Unapologetic": A Qualitative Study of Mystical Experience in Ordinary Life - Mc Cann, Kimberly (The international journal of religion and spirituality in society, 2020)
This study reviews lived experiences (secular and religious) reported by participants as being mystical or having characteristics of mysticism. Experiencing a mystical state however, is not a "one size fits all" formula. Instead, the experiences described by this sample were uniquely contextualized by particular situation(s), participant language, and personal history. All experiences were characterized by W.T. Stace’s qualities of mystical experience, but no single activity was responsible for triggering any of the events. The intent of trigger influence has been described as the process of doing whatever necessary to enter the individual into a trance or holotropic state of consciousness. The two major themes associated with these experiences were Openness to Experience and Life Transition.